Uganda’s First 100 COVID-19 Cases: Trends and Lessons - Olum, Ronald; Bongomin, Felix (International Journal of Infectious Diseases, 2020)
Coronavirus disease -2019 (COVID-19) continues to hit-hard on many countries across the world. Uganda reported its first case of COVID-19 on the March 21, 2020 [1]. A 36-year-old businessman from Kampala, Uganda’s capital, who had travelled to Dubai, United Arab Emirates (UAE) in a healthy condition four days prior to his return. He presented with fever and flu-like symptoms at Entebbe International Airport (EIA) and his sample tested positive for SARS-CoV-2, the causative agent of COVID-19 [1]. Consequently, individuals who had been to UAE two weeks prior to the first case were traced by Ministry of Health (MoH) Uganda and subjected to institutional quarantine. In the following two weeks (March 21 to April 5), there was a rapid rise in the number of cases to 52, most of whom were imported cases from institutional quarantine, Figure 1. The epidemiologic curve had flattened between April 5 to April 19. However, we observed a second upsurge in incident cases during the late April and early May ultimately reaching 100 cases on May 6, 2020, Figure 1 [2]. Of these, 89 cases (89%) were imported, 8 (8%) local transmissions and 3 (3%) with unknown chain of transmission. Majority of the cases were truck drivers (40, 40%) from Kenya (21) and Tanzania (14) with 3 Ugandans, 1 Eritrean and 1 Burundian. The truck drivers transit through Uganda, carrying cargo to or from neighbouring countries who have all recorded rises in cases of late [3]. In addition to the truck drivers, two cases of local transmission have been reported among Uganda Police Force officers, which may indicate an on-going community transmission of COVID-19
Keywords: COVID-19 Cases; Trends; Lessons